Dermoscopy in Vitiligo: An emerging armamentarium in diagnosis and activity assessment - Guneet Awal; Jasleen Kaur; Komalpreet Kaur (Wolters Kluwer Medknow Publications, 2022)
Context: Vitiligo is an autoimmune depigmentary disorder characterized by loss of epidermal melanocytes. It can be diagnosed clinically, however, dermoscopy aids in its differentiation from other hypopigmentary and depigmentary conditions and also helps in evaluating disease activity. Aims: To study the dermoscopic patterns of vitiligo and evaluate their correlation with disease activity. Settings and Design: This is a cross-sectional and observational study conducted in the outpatient department of dermatology of a tertiary care hospital at Sri Amritsar. Methods and Materials: Fifty patients complaining of depigmented lesions were diagnosed clinically for vitiligo. Histopathological confirmation was done in difficult to diagnose cases. Patients with clinically stable vitiligo, unstable vitiligo, and vitiligo under treatment were included. A dermoscopic examination was done with a Dermlite DL4 dermoscope. The photographs were taken using a standard phone and the dermoscopic findings were documented.Statistical Analysis Used: The results were tabulated and expressed as percentages. The Pearson correlation coefficient was calculated between dermoscopic patterns of vitiligo and disease activity. Results: On examination with the dermoscope, pigmentary patterns observed were marginal hyperpigmentation, perifollicular pigmentation, reticulate hyperpigmentation, and altered pigment network. Morphological patterns seen on dermoscopy included leukotrichia, micro-Koebner phenomena, polka dots, and starburst appearance. Conclusions: Marginal hyperpigmentation, perifollicular pigmentation, and reticulate pigmentation were the markers of disease stability. Leukotrichia was seen in patients of stable vitiligo majority being treatment refractory. Altered pigment network, micro-Koebner phenomena, starburst appearance, and polka dots indicated unstable vitiligo. Presence of erythema and telangiectasias indicated response to treatment. Hence, dermoscopy can be used as an effective tool for the diagnosis of vitiligo and evaluation of disease activity.